Identification of potential susceptibility genes in patients with primary Sjögren’s syndrome-associated pulmonary arterial hypertension through whole exome sequencing - Li, Mucong; Shi, Yue; Zhao, Jiuliang; Wang, Qian; Li, Mengtao; Zhao, Xiuli (Arthritis research & therapy, 2023)
Background Pulmonary arterial hypertension (PAH) is a rare complication of primary Sjögren's syndrome (pSS). Several genes have proven to be associated with pSS and PAH. However, there is no study specifically addressing the genetic susceptibility in pSS combined with PAH. Methods Thirty-four unrelated patients with pSS-PAH were recruited from April 2019 to July 2021 at Peking Union Medical College Hospital. Demographic and clinical data were recorded in detail, and peripheral blood samples were collected for whole-exome sequencing (WES). Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed to predict the functional effect of mutant genes. Genetic variants identified by WES were confirmed by polymerase chain reaction (PCR)-Sanger sequencing. Results We totally identified 141 pathogenic variant loci of 129 genes in these 34 pSS-PAH patients, using WES analysis. Patients with a family history of rheumatic diseases are more likely to carry FLG mutations or carry gene variations related to the biosynthesis of the amino acids pathway (p < 0.05). According to Sanger sequencing confirmation and pathogenicity validation, we totally identified five candidate pathogenic variants including FLG c.12064A > T, BCR c.3275_3278dupCCGG, GIGYF2 c.3463C > A, ITK c.1741C > T, and SLC26A4 c.919-2A > G. Conclusion Our findings provide preliminary data of exome sequencing to identify susceptibility loci for pSS-PAH and enriched our understanding of the genetic etiology for pSS-PAH. The candidate pathogenic genes may be the potential genetic markers for early warning of this disease. Keywords: Primary Sjögren's syndrome, Pulmonary arterial hypertension, Whole-exome sequencing, FLG, BCR, GIGYF2, ITK, SLC26A4